ANALISIS KUALITAS AIR SUMUR BOR DENGAN VARIASI WAKTU PENGAMBILAN SAMPEL DI JALAN PENDIDIKAN, MALAINGKEDI, KECAMATAN SORONG MANOI, KOTA SORONG, PAPUA BARAT DAYA.: Analisis Kualitas Air Sumur Bor - Arbiatun, Fatimah; Way, Jhose Rizal; Towansiba, Irmando Risman (Casuarina: Jurnal Teknik Lingkungan, 2024)
This research aimed to analyze the quality of borewell water widely utilized by the community on Jalan Pendidikan KM 8, Malaingkedi, Sorong Manoi District, Sorong City, West Papua. Water samples were collected at three different times, namely 09.00, 14.00, and 17.00. The parameters tested included physical parameters such as color, odor, TDS (Total Dissolved Solids), conductivity, salinity and chemical parameters such as pH. The results showed that in general, the quality of the borewell water still met the quality standards for clean water according to the Indonesian Ministry of Health Regulation No. 32 of 2017. The average values were 315.67 μS/cm for conductivity, 207 ppm for TDS, 157 ppm for salinity, and 8.47 for pH. There were variations in the values for each tested parameter, but they were still within the permitted range. However, some parameters such as slightly turbid water color and pH values slightly exceeding the ideal range were observed. Regular water quality monitoring and pollution control efforts are essential to ensure the availability of safe clean water for the community.